Tantangan Dakwah: Tinjauan Faktual Kekosongan Dai Pada Bulan Suci Ramadhan Di Masjid Darussalam Kampung Pisang Kota Sorong - Sitti Mutia Faradillah (UPT Pusat Studi Aswaja UNISNU Jepara, 2022)
AbstractThe purpose of the study to examine the factors causing the constrained activities of da'wah in the holy month of Ramadan in the Darussalam Mosque Kampung Pisang Sorong City west Papua. The da'wah activity in question is a routine lecture by the dai (preachers) conducted every night of ramadan that has been programmed by the Ministry of Religious Affairs of Sorong City. This research uses qualitative research type. As for data collection, researchers use interview methods to primary informants, namely the management of The Darussalam Mosque Kampung Pisang, the dai / mubaligh listed in the schedule of lectures, worshipers (mad'u) Darussalam Mosque Kampung Pisang, and the Ministry of Religious Affairs that compiled the schedule of the lecture.As for the observation method, the author directly observes the situation in the field both from BKM / the manager of The Darussalam Mosque Kampung Pisang, Jamaah (mad'u) Masjid Darussalam Kampung Pisang, the dais listed in the lecture schedule, and the Ministry of Religion.This research is expected to be a reference in overcoming the vacancy according to the causative factors in the holy month of Ramadan throughout the Mosque, especially in the Darussalam Mosque Kampung Pisang. Thus da'wah activities can run well without any obstacles.Keywords: Dai and his personality, the cause of the vacancy dai, the efforts of the Ministry of ReligionAbstrakTujuan penelitian untuk mengkaji faktor-faktor penyebab terhambatnya kegiatan dakwahdi bulan suci Ramadhan di Masjid Darussalam Kampung Pisang Kota Sorong Papua Barat. Kegiatan dakwah yang dimaksud adalah pengajian rutin oleh para dai yang dilakukan setiap malam Ramadhan yang telah diprogramkan oleh Kementerian Agama Kota Sorong. Penelitian ini menggunakan jenis penelitian kualitatif. Adapun untuk pengumpulan data, peneliti menggunakan metode wawancara kepada informan utama yaitu pengurus Masjid Darussalam Kampung Pisang, para dai/mubaligh yang tercantum dalam jadwal perkuliahan, jamaah (mad'u) Masjid Darussalam Kampung Pisang, dan Kementerian Agama. Urusan yang menyusun jadwal kuliah. Adapun metode observasi, penulis mengamati secara langsung keadaan di lapangan baik dari BKM/pengelola Masjid Darussalam Kampung Pisang, Jamaah (mad'u) Masjid Darussalam Kampung Pisang, mimbar yang tercantum dalam jadwal perkuliahan, dan Kementerian Agama. Penelitian ini diharapkan dapat menjadi acuan dalam mengatasi kekosongan menurut faktor penyebabnya pada bulan suci Ramadhan di seluruh Masjid khususnya Masjid Darussalam Kampung Pisang. Dengan demikian kegiatan dakwah dapat berjalan dengan baik tanpa ada hambatan.Kata kunci: Dai dan kepribadiannya, penyebab kekosongan dai, Kementerian Agama